2002
DOI: 10.1302/0301-620x.84b3.11609
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave promotes growth and differentiation of bone-marrow stromal cells towards osteoprogenitors associated with induction of TGF-β1

Abstract: Extracorporeal shock-wave (ESW) treatment has been shown to be effective in promoting the healing of fractures. We aimed to determine whether ESW could enhance the growth of bone-marrow osteoprogenitor cells. We applied ESW to the left femur of rats 10 mm above the knee at 0.16 mJ/mm2 in a range of between 250 and 2000 impulses. Bone-marrow cells were harvested after ESW for one day and subjected to assessment of colony-forming unit (CFU) granulocytes, monocytes, erythocytes, megakaryocytes (CFU-Mix), CFU-stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
70
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(83 citation statements)
references
References 33 publications
3
70
0
10
Order By: Relevance
“…Treatment with 500 shocks proved to be within the safe range in the energy intensity of 0.17mJ/mm 2 ( Figure 4A). 19,20 Further, we found that pathologic expression of MMPs 1 and 13 and IL-6 was decreased in diseased cells with shock wave treatment.…”
Section: Discussionmentioning
confidence: 71%
“…Treatment with 500 shocks proved to be within the safe range in the energy intensity of 0.17mJ/mm 2 ( Figure 4A). 19,20 Further, we found that pathologic expression of MMPs 1 and 13 and IL-6 was decreased in diseased cells with shock wave treatment.…”
Section: Discussionmentioning
confidence: 71%
“…It has been recently demonstrated that, in addition to angiogenesis due to migration and proliferation of endothelial cells in situ, EPCs contribute to neovascularization in ischemic tissue through a vasculogenetic mechanism and through secretion of a variety of angiogenic factors [18][19]. Finally, recent studies have marked out that ESW are able to recruit stem cells and to stimulate their differentiation in various damaged tissues inducing reparative phenomena [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…The successful treatment of bony non-union when using ESWA was thought to be related to CP by causing microfractures and stimulating healing [5]. However, molecular biological investigations in rat femurs exposed to ESW demonstrated the stimulation of bone-marrow stromal growth and its differentiation towards osteoprogenitors through the induction of tumor growth factor (TGF-b1) [6]. Similar findings in a segmental bone defect model indicated a predominant chemotactic and…”
Section: Introductionmentioning
confidence: 94%